Metal compound containing silafluorene group, olefin polymerization catalyst and preparation and application thereof

By using metal composites containing silicon heterofluorenyl groups in olefin polymerization catalysts, the problems of existing catalyst stability and efficiency are solved, higher activity and melting index are achieved, the oligomer and hexane extractable content are reduced, and the product quality is improved.

CN119661748AActive Publication Date: 2025-03-21CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202311206696.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-19
Publication Date
2025-03-21
Estimated Expiration
2043-09-19

AI Technical Summary

Technical Problem

The existing olefin polymerization catalysts have problems such as being difficult to guarantee the stability of solid feeding, being electrostatically sensitive to impurities, being low in efficiency, high ash content, high catalyst cost per unit product, and affecting the quality of film products.

Method used

A metal composite containing silicon heterofluorene group was developed to form a highly dispersible catalyst for olefin polymerization by supporting metal catalytic components and silicon heterofluorene group on an ultrafine inorganic oxide support.

Benefits of technology

The activity and melt index of the catalyst are improved, the oligomer content and hexane extract content in the polymer are reduced, and the stability of the catalyst and the quality of the film products are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004456271490000101
    Figure BDA0004456271490000101
Patent Text Reader

Abstract

The invention discloses a metal compound containing a silafluorene group, an olefin polymerization catalyst containing the metal compound as well as a preparation method and application of the olefin polymerization catalyst. The metal compound contains a main compound which is a metal compound containing a silafluorene group, and the metal compound is a mixture of metal halide, a dialkyl silafluorene compound and an electron donor compound and / or a reaction product of the components, wherein the contained silafluorene group enables the catalyst containing the silafluorene group to have higher activity. The main body compound is loaded on an inorganic oxide carrier in a specific particle size range to obtain a high-dispersity catalyst, the catalyst can be used for olefin polymerization reaction, and a polymer obtained by polymerization has a relatively high melt index and low oligomer content.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of olefin polymerization catalysts, and in particular relates to a metal complex containing a silicon heterofluorene group, an olefin polymerization catalyst containing the metal complex, and a preparation method and application thereof. Background Art

[0002] The main catalyst used in the Unipol process unit of Univation Company to produce polyethylene in the early stage was the M-1 catalyst (UCAT-A) with silica gel as the carrier. Because silica gel is used as the carrier, the fluidity and mechanical strength of the catalyst are relatively high, and the direct application in the gas phase fluidized bed has a better effect, and the particle properties of the polymer can be controlled to a certain extent. However, with the continuous production practice, the M-1 catalyst has shown that the stability of solid feeding is difficult to ensure, and the catalyst system is prone to blockage and bridging. At the same time, the catalyst is highly sensitive to electrostatics caused by impurities in the reaction system, causing reactor flakes and agglomerations; and the M-1 type catalyst has a low efficiency, and its resin product has a high ash content, resulting in a high catalyst cost per unit product and affecting the quality of the film product. In the 1990s, Univation developed a slurry catalyst-J catalyst (UCAT-J) to replace the original M-1 catalyst, and promoted its application at home and abroad. At present, the UCAT-J catalyst has replaced the M-1 catalyst and become a new development direction of the Unipol process.

[0003] Chinese patent CN106543303A relates to a catalyst component for olefin polymerization, a catalyst and a preparation method thereof. The catalyst component comprises: 1) an ultrafine inorganic oxide carrier, and 2) a reaction product of a magnesium halide, a halogenated hydrocarbon, a titanium halide and an electron donor compound. The catalyst comprises the reaction product of the following components: (A) the catalyst component of the present invention; and (B) a catalyst having the general formula AlR n X 3-n The organic aluminum compound is an organic aluminum compound, wherein R is hydrogen or a hydrocarbon group having 1 to 20 carbon atoms, X is a halogen, preferably chlorine, bromine or iodine, and 0<n≤3. The catalyst of the present invention has high activity, and the obtained polymer has a higher bulk density and a higher melt index. However, the catalyst prepared by the scheme has a high content of hexane extractables in the polymer powder generated by ethylene homopolymerization, which has an adverse effect on industrial production.

[0004] Chinese patent CN100389134A provides a catalyst component for ethylene polymerization or copolymerization, which comprises a solid containing magnesium / titanium, loaded with at least one transition metal titanium compound, at least one suitable electron donor, and at least one hydrogen performance improver. The catalyst containing the catalyst component has the characteristics of particularly good hydrogen sensitivity, high catalytic activity, good catalyst and polymer particle morphology, low fine powder content, etc., and is very suitable for ethylene slurry and gas phase polymerization processes, especially for the production process of producing ethylene polymers with wide molecular weight distribution using dual reactors. It is characterized in that it comprises a catalyst component obtained by loading at least one transition metal titanium compound, at least one electron donor and at least one hydrogen performance improver on a solid containing titanium / magnesium; the electron donor is aliphatic ether, aromatic ether, cycloaliphatic ether and aliphatic ketone; the general formula of the transition metal titanium compound is Ti(OR) a X b , wherein R is a C1-C14 aliphatic hydrocarbon group or an aromatic hydrocarbon group, X is a halogen atom, a is an integer from 0 to 2, b is an integer from 0 to 4, and a+b=3 or 4; the hydrogen adjustment performance improver is silicon tetrachloride. This solution reduces the oligomer content in the polymer, but the activity of the catalyst is not high enough.

[0005] Chinese patent CN1493599A discloses an improved catalyst for ethylene polymerization, which improves the catalyst activity and reduces the oligomer content in the polymer by adding alkyl silicate in the mother liquor preparation of the catalyst main catalytic component. However, the activity of the catalyst is not high enough.

[0006] Therefore, there is an urgent need to develop a catalyst for olefin polymerization with higher activity and melt index and low oligomer content in the polymer. Summary of the invention

[0007] In view of the technical problems existing in the prior art, the present invention provides a metal composite containing a silicon heterofluorene group, and an olefin polymerization catalyst using the composite. The metal composite containing a silicon heterofluorene group comprises an ultrafine inorganic oxide carrier and a host compound, wherein the host compound contains a metal catalytic component and a silicon heterofluorene group, so that the catalyst containing the metal composite has higher activity. The host compound is loaded on an inorganic oxide carrier with a specific particle size range to obtain a highly dispersible catalyst, which can be used for olefin polymerization.

[0008] One of the purposes of the present invention is to provide a metal composite containing silicon heterofluorene groups, comprising: an ultrafine carrier, and a metal compound containing silicon heterofluorene groups supported on the ultrafine carrier, wherein the ultrafine carrier is selected from at least one of ultrafine silica and ultrafine alumina, preferably ultrafine silica; and the metal contains magnesium and titanium.

[0009] According to the present invention, in the metal composite containing silicon heterofluorene groups:

[0010] Based on the total weight of the metal composite containing silicon heterofluorene groups as 100 parts, the ultrafine carrier is 10 to 55 parts, and the metal compound containing silicon heterofluorene groups is 45 to 90 parts; preferably, based on the total weight of the metal composite containing silicon heterofluorene groups as 100 parts, the ultrafine carrier is 10 to 35 parts, and the metal compound containing silicon heterofluorene groups is 65 to 90 parts; more preferably, based on the total weight of the metal composite containing silicon heterofluorene groups as 100 parts, the ultrafine carrier is 15 to 30 parts, and the metal compound containing silicon heterofluorene groups is 70 to 85 parts;

[0011] In the metal composite containing silicon heterofluorene groups, the content of titanium is 0.2-3.5wt%, for example, it can be 0.2, 0.5, 1, 1.5, 2, 2.5, 3 or 3.5wt%, or a value or a range of values ​​between any two of the above values; preferably, in the metal composite containing silicon heterofluorene groups, the content of titanium is 0.8-2.8wt%, more preferably, in the metal composite containing silicon heterofluorene groups, the content of titanium is 1.9-2.5wt%;

[0012] The particle size of the ultrafine carrier can be selected in a wide range. Preferably, the particle size of the ultrafine carrier is 0.5nm to 8μm, preferably 1nm to 3μm, and more preferably 15nm to 1.5μm. The inorganic oxide in this particle size range makes the catalyst loaded with dialkylsilicon heterofluorene compound have good particle quality, high strength, and is not easy to break. The ultrafine inorganic oxide carrier in the present invention can be in solid form or in dispersed liquid form when used, such as commercially available silica gel products.

[0013] According to the present invention, in the metal composite containing silicon heterofluorene groups, the metal compound containing silicon heterofluorene groups is a mixture of metal halides, dialkyl silicon heterofluorene compounds, electron donor compounds and / or a reaction product of the above components.

[0014] According to an embodiment of the present invention, in the metal compound containing silicon heterofluorene group:

[0015] The metal halide comprises magnesium halide and titanium halide; wherein the magnesium halide is selected from at least one of magnesium chloride, magnesium bromide and magnesium iodide, and the titanium halide is selected from at least one of titanium trichloride, titanium tetrachloride, titanium tribromide and titanium tetrabromide, preferably at least one of titanium trichloride and titanium tetrachloride;

[0016] The general formula of the dialkylsilylfluorene compound is R 1 R 2Silafluorene, wherein Silafluorene is a silanol group; R 1 , R 2 The same or different, independently selected from C1-C10 saturated or unsaturated hydrocarbon groups, C3-C10 cycloalkyl groups or C6-C18 aryl groups, preferably C1-C6 saturated alkyl groups, C3-C8 cycloalkyl groups or C6-C12 aryl groups; specifically, the dialkyl silafluorene compound is selected from at least one of 9,9-dimethyl-9H-9-silafluorene and 9,9-diphenyl-9H-9-silafluorene;

[0017] The electron donor compound is selected from at least one of esters, ethers, and ketones, and is preferably selected from at least one of alkyl esters of C1-C8 saturated fatty carboxylic acids, alkyl esters of C7-C12 aromatic carboxylic acids, C2-C8 fatty ethers, C3-C8 cyclic ethers, and C3-C10 saturated fatty ketones; specifically, the electron donor compound is selected from at least one of methyl formate, ethyl formate, isopropyl formate, n-propyl formate, methyl acetate, ethyl acetate, n-propyl acetate, isopropyl acetate, n-butyl acetate, isobutyl acetate, ethyl ether, propyl ether, hexyl ether, tetrahydrofuran, acetone, and methyl isobutyl ketone, and is preferably selected from at least one of methyl formate, ethyl acetate, n-butyl acetate, ethyl ether, hexyl ether, tetrahydrofuran, acetone, and methyl isobutyl ketone.

[0018] The second object of the present invention is to provide a method for preparing the metal composite containing silicon heterofluorene groups, comprising: uniformly mixing a slurry containing the ultrafine carrier and the metal compound containing silicon heterofluorene groups, and drying to obtain the metal composite containing silicon heterofluorene groups. Specifically, the preparation method comprises the following steps:

[0019] (1) reacting components including magnesium halide, titanium halide, dialkyl silane compound, and electron donor compound to obtain a mother solution of a metal compound containing a silane group;

[0020] (2) then adding an ultrafine carrier and mixing to obtain a slurry;

[0021] (3) The obtained slurry is spray-dried to obtain the metal composite containing silicon heterofluorene groups.

[0022] According to the present invention, in the method for preparing the metal composite containing silicon heterofluorene groups:

[0023] Based on 1 mol of the titanium halide, the magnesium halide is 0.4 to 20 mol, preferably 1 to 12 mol, more preferably 2 to 10 mol; the dialkylsilylfluorene compound is 0.02 to 12 mol, preferably 0.05 to 8 mol, more preferably 0.1 to 5 mol; the electron donor compound is 1 to 450 mol, preferably 35 to 250 mol, more preferably 110 to 200 mol;

[0024] The reaction conditions in step (1) are: reaction temperature is 65-85° C., and reaction time is 2-5 h;

[0025] In the step (2), the amount of the ultrafine carrier in the slurry is such that after the carrier and the mother liquor are mixed, a slurry suitable for spray drying can be formed. Preferably, the content of the ultrafine carrier in the slurry is 0.5 to 50 wt%, preferably 1 to 30 wt%;

[0026] In the step (3), the spray drying can adopt the spray drying equipment and drying process conditions commonly used in the art. Preferably, the spray drying conditions include: an inlet temperature of 90 to 240°C, preferably 110 to 200°C; an outlet temperature of 70 to 130°C, preferably 95 to 110°C.

[0027] A third object of the present invention is to provide an olefin polymerization catalyst comprising:

[0028] Component (A): an organoaluminum compound;

[0029] Component (B): the metal complex containing silicon heterofluorene groups or the metal complex containing silicon heterofluorene groups obtained by the above preparation method.

[0030] According to the present invention, in the olefin polymerization catalyst:

[0031] The general formula of the organoaluminum compound of component (A) is AlR n X 3-n , wherein R is a C1-C18 hydrocarbon group, X is chlorine, bromine or iodine, and 0<n≤3; preferably, the organoaluminum compound is selected from at least one of triethylaluminum, triisobutylaluminum, tri-n-hexylaluminum, tri-n-octylaluminum, and diethylaluminum monochloride;

[0032] The molar ratio of the component (A) to the component (B) is (5-450):1, preferably (15-250):1, wherein the component (A) is calculated based on the aluminum element contained therein, and the component (B) is calculated based on the titanium element contained therein.

[0033] A fourth object of the present invention is to provide a method for preparing the above-mentioned olefin polymerization catalyst, comprising: mixing components including the above-mentioned organic aluminum compound and the above-mentioned metal complex containing silicon heterofluorene groups to obtain the above-mentioned olefin polymerization catalyst.

[0034] A fifth object of the present invention is to provide an olefin polymerization catalyst as described above or an olefin polymerization catalyst obtained by the above preparation method for use in olefin polymerization reactions.

[0035] Specifically, the olefin polymerization catalyst is first activated before being used in the olefin polymerization reaction. For example, the olefin polymerization catalyst is added to an activator for activation, and then the olefin polymerization reaction is initiated. Preferably, the activator is selected from hydrocarbon organic solvents, preferably at least one of isopentane, hexane, heptane, toluene, xylene, petroleum naphtha, and mineral oil.

[0036] The catalyst of the present invention is suitable for olefin polymerization, especially olefin polymerization containing ethylene, which can be homopolymerization of various ethylenes or copolymerization of ethylene and alpha-olefins, wherein the alpha-olefin can be selected from one of propylene, butene, pentene, hexene, octene and 4-methylpentene-1. Its polymerization process can adopt gas phase method, slurry method and solution method, and is more suitable for gas phase fluidized bed polymerization. The conditions for olefin polymerization can be conventionally selected according to the prior art, and no further description is given here. In order to make the solid catalyst component obtained after spray drying suitable for the production of ethylene polymers, an organic aluminum compound must be added as an activator component to reduce the titanium atom in the catalyst component to a state that can effectively polymerize ethylene. Generally, in a hydrocarbon solvent, the above-mentioned catalyst component and the activator component are reacted to obtain a catalyst for olefin polymerization; the above-mentioned catalyst component and the activator component can also be added to a hydrocarbon solvent during the polymerization process to react, and then the olefin polymerization reaction is initiated.

[0037] The catalyst for olefin polymerization of the present invention comprises an organic aluminum compound and a metal complex containing a silicon heterofluorene group, wherein the metal complex containing a silicon heterofluorene group uses an ultrafine inorganic oxide as a carrier to load the metal compound containing a silicon heterofluorene group. In the present invention, an electron donor compound is used to dissolve magnesium halide, and a dialkyl silicon heterofluorene compound and a titanium halide are added to react to obtain a mother liquor, and after adding an ultrafine carrier, the metal complex containing a silicon heterofluorene group is obtained by spray molding. The polymer prepared by the catalyst of the metal complex containing a silicon heterofluorene group in the present invention has a high melt index, low hexane extract and low oligomer content. The multi-ring ladder-shaped π-conjugated molecular structure contained in the dialkyl silicon heterofluorene compound has a strong electron donating effect, so that the polymerization efficiency of the active center of the catalyst can be effectively improved after the silicon atom is coordinated with the active center. DETAILED DESCRIPTION

[0038] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.

[0039] The test instruments and test conditions used in the examples are as follows:

[0040] 1. Catalyst activity: expressed as the weight of polymer obtained per gram of catalyst;

[0041] 2. Polymer melt index (MI): 6932 melt index tester, CEAST, Italy;

[0042] 3. Hexane extractable content in polymer powder (wt%): The dried polymer powder is extracted with hexane, specifically, the polymer is eluted with hexane for 4 hours. The percentage of the weight difference of the polymer powder before and after extraction to the weight of the polymer powder before extraction is the hexane extractable content in the polymer powder;

[0043] 4. Determination of titanium content in catalyst components: Dissolve the catalyst sample with 1M sulfuric acid, measure the dissolved solution with a spectrophotometer, and calculate the titanium content using the working curve;

[0044] 5. The content of ultrafine inorganic oxide is obtained by calculating the ratio of feed amount to output catalyst mass.

[0045] The raw materials used in the examples are all commercially available products.

[0046] Example 1

[0047] (1) Preparation of metal complexes containing silicon heterofluorene groups

[0048] Into a 250mL three-necked flask purged with nitrogen, 1.8g TiCl4, 4.8g anhydrous MgCl2, 1.7g 9,9-dimethyl-9H-9-silafluorene and 120mL tetrahydrofuran were added successively, the temperature was raised to 65°C with stirring, the reaction was carried out at this temperature for 3 hours, and the temperature was lowered to 35°C to obtain a mother liquor.

[0049] Into a 250mL three-necked flask purged with nitrogen, add 7 grams of silica gel (Cabot Corporation TS-610, particle size 0.02-0.1um), add the cooled mother liquor, maintain the temperature at 35°C, stir for 1 hour, and then spray dry the mother liquor mixed with silica gel using a spray dryer. The spraying conditions are: inlet temperature 195°C, outlet temperature 110°C, to obtain a catalyst component with a titanium content of 2.24wt% and a silicon dioxide content of 25wt%.

[0050] (2) Ethylene slurry polymerization

[0051] 1L of hexane was added to a 2L polymerization reactor purged with nitrogen, and 1mL of 1M triethylaluminum / hexane and 0.02g of catalyst were added at the same time. The temperature was raised to 75°C and hydrogen was added at 0.18Mpa. After hydrogenation, 0.75Mpa of ethylene was added. The temperature was raised to 85°C, and the reaction was continued for 2 hours before the temperature was lowered and the material was discharged. The polymerization results are shown in Table 1.

[0052] Example 2

[0053] (1) Preparation of catalyst system

[0054] The same as Example 1, except that the reaction temperature was adjusted to 85° C., the reaction time was adjusted to 4 hours, and the titanium content of the obtained catalyst component was 2.26 wt %, and the silicon dioxide content was 23 wt %.

[0055] (2) Ethylene slurry polymerization

[0056] Same as Example 1, the polymerization results are shown in Table 1.

[0057] Example 3

[0058] (1) Preparation of catalyst system

[0059] The same as Example 1, except that the spray inlet temperature was adjusted to 170°C, the outlet temperature was 100°C, and the titanium content of the obtained catalyst component was 2.15wt%, and the silicon dioxide content was 22wt%.

[0060] (2) Ethylene slurry polymerization

[0061] Same as Example 1, the polymerization results are shown in Table 1.

[0062] Example 4

[0063] (1) Preparation of catalyst components

[0064] The same as Example 1, except that the amount of 9,9-dimethyl-9H-9-silafluorene used is 3.4 g, and the titanium content of the obtained catalyst component is 2.27 wt%, and the silicon dioxide content is 23 wt%.

[0065] (2) Ethylene slurry polymerization

[0066] The same as Example 1, except that the metal complex containing silicon heterofluorene group obtained in the above step (1) was added. The polymerization results are shown in Table 1.

[0067] Example 5

[0068] (1) Preparation of catalyst components

[0069] The same as Example 1, except that the amount of 9,9-dimethyl-9H-9-silafluorene used is 0.8 g, and the titanium content of the obtained catalyst component is 2.09 wt%, and the silicon dioxide content is 24 wt%.

[0070] (2) Ethylene slurry polymerization

[0071] The same as Example 1, except that the metal complex containing silicon heterofluorene group obtained in the above step (1) was added. The polymerization results are shown in Table 1.

[0072] Example 6

[0073] (1) Preparation of catalyst components

[0074] The same as Example 1, except that 9,9-dimethyl-9H-9-silafluorene is replaced by 9,9-diphenyl-9H-9-silafluorene in an amount of 1.4 g. The titanium content of the obtained catalyst component is 2.19 wt%, and the silicon dioxide content is 22 wt%.

[0075] (2) Ethylene slurry polymerization

[0076] The same as Example 1, except that the metal complex containing silicon heterofluorene group obtained in the above step (1) was added. The polymerization results are shown in Table 1.

[0077] Comparative Example 1

[0078] (1) Preparation of catalyst components

[0079] Into a 250mL three-necked flask purged with nitrogen, 1.8g TiC14, 4.8g anhydrous MgCl2 and 120mL tetrahydrofuran were added successively, the temperature was raised to 65°C with stirring, the reaction was carried out at this temperature for 3 hours, and the temperature was lowered to 35°C to obtain a mother liquor.

[0080] Into a 250mL three-necked flask purged with nitrogen, add 7g of silica gel (Cabot Corporation TS-610, particle size of 0.02-0.1 micron), add the cooled mother liquor, maintain the temperature at 35°C, stir for 1 hour, and then spray dry the mother liquor mixed with silica gel using a spray dryer. The spraying conditions are: inlet temperature 195°C, outlet temperature 110°C, to obtain a catalyst component with a titanium content of 2.2wt% and a silicon dioxide content of 25wt%.

[0081] (2) Ethylene slurry polymerization

[0082] 1L of hexane was added to a 2L polymerization reactor purged with nitrogen, and 2mL of 1M triethylaluminum / hexane and 0.01g of catalyst were added at the same time. The temperature was raised to 75°C and hydrogen was added at 0.18Mpa. After hydrogenation, 0.75Mpa of ethylene was added. The temperature was raised to 85°C, and after reacting for 2 hours, the temperature was lowered and the material was discharged. The polymerization results are shown in Table 1.

[0083] Table 1. Catalyst performance obtained in Examples and Comparative Examples

[0084]

[0085] It can be seen from the polymerization data in Table 1 that under the same polymerization conditions, compared with Comparative Example 1, the polycyclic trapezoidal π-conjugated molecular structure contained in the silafluorene group in the example catalyst enables the silicon atom to coordinate with the active center to effectively improve the polymerization efficiency of the catalyst active center, and the obtained catalyst activity is higher, the obtained polymer has a higher melt index, and the hexane extractable content is lower.

[0086] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.

Claims

1. A metal composite containing a silicon heterofluorene group, comprising: An ultrafine carrier, and a metal compound containing a silicon heterofluorene group supported on the ultrafine carrier, wherein the ultrafine carrier is selected from at least one of ultrafine silicon dioxide and ultrafine aluminum oxide, and the metal contains magnesium and titanium.

2. The metal composite according to claim 1, characterized in that Based on 100 parts of the total weight of the metal composite containing silicon heterofluorene groups, the ultrafine carrier is 10 to 55 parts, and the metal compound containing silicon heterofluorene groups is 45 to 90 parts; preferably, based on 100 parts of the total weight of the metal composite containing silicon heterofluorene groups, the ultrafine carrier is 10 to 35 parts, and the metal compound containing silicon heterofluorene groups is 65 to 90 parts; and / or, The content of titanium in the metal composite containing silicon heterofluorene groups is 0.2 to 3.5 wt%, preferably 0.8 to 2.8 wt%; and / or, The particle size of the ultrafine carrier is 0.5 nm to 8 μm, preferably 1 nm to 3 μm.

3. The metal composite according to claim 1, characterized in that The ultrafine carrier is ultrafine silicon dioxide; and / or, The metal compound containing silafluorene groups is a mixture of metal halides, dialkyl silafluorene compounds, electron donor compounds and / or a reaction product of the above components.

4. The metal composite according to claim 3, characterized in that The metal halide comprises magnesium halide and titanium halide; and / or, The general formula of the dialkylsilylfluorene compound is R 1 R 2 Silafluorene, wherein Silafluorene is a silanol group; R 1 , R 2 the same or different, independently selected from C1-C10 saturated or unsaturated hydrocarbon groups, C3-C10 cycloalkyl groups or C6-C18 aryl groups, preferably C1-C6 saturated alkyl groups, C3-C8 cycloalkyl groups or C6-C12 aryl groups; and / or, The electron donor compound is selected from at least one of esters, ethers and ketones, preferably at least one of alkyl esters of C1-C8 saturated fatty carboxylic acids, alkyl esters of C7-C12 aromatic carboxylic acids, C2-C8 fatty ethers, C3-C8 cyclic ethers and C3-C10 saturated fatty ketones.

5. The metal composite according to claim 4, characterized in that The magnesium halide is selected from at least one of magnesium chloride, magnesium bromide and magnesium iodide; and / or, The titanium halide is selected from at least one of titanium trichloride, titanium tetrachloride, titanium tribromide and titanium tetrabromide, preferably at least one of titanium trichloride and titanium tetrachloride; and / or, The dialkyl silafluorene compound is selected from at least one of 9,9-dimethyl-9H-9-silafluorene and 9,9-diphenyl-9H-9-silafluorene; and / or, The electron donor compound is selected from at least one of methyl formate, ethyl formate, isopropyl formate, n-propyl formate, methyl acetate, ethyl acetate, n-propyl acetate, isopropyl acetate, n-butyl acetate, isobutyl acetate, ethyl ether, propyl ether, hexyl ether, tetrahydrofuran, acetone, and methyl isobutyl ketone, and is preferably selected from at least one of methyl formate, ethyl acetate, n-butyl acetate, ethyl ether, hexyl ether, tetrahydrofuran, acetone, and methyl isobutyl ketone.

6. A method for preparing the metal composite containing silicon heterofluorene groups according to any one of claims 1 to 5, comprising: The slurry containing the ultrafine carrier and the metal compound containing silicon heterofluorene groups is mixed evenly and then dried to obtain the metal composite containing silicon heterofluorene groups.

7. The preparation method according to claim 6, characterized in that: The preparation method specifically comprises the following steps: (1) reacting components including magnesium halide, titanium halide, dialkyl silane compound, and electron donor compound to obtain a mother solution of a metal compound containing a silane group; (2) then adding an ultrafine carrier and mixing to obtain a slurry; (3) The obtained slurry is spray-dried to obtain the metal composite containing silicon heterofluorene groups.

8. The preparation method according to claim 7, characterized in that: Based on 1 mol of the titanium halide, the magnesium halide is 0.4-20 mol, preferably 1-12 mol; the dialkylsilylfluorene compound is 0.02-12 mol, preferably 0.05-8 mol; the electron donor compound is 1-450 mol, preferably 35-250 mol; and / or, The reaction conditions in step (1) are: reaction temperature of 65 to 85° C., and / or, reaction time of 2 to 5 h; and / or, In the step (2), the content of the ultrafine carrier in the slurry is 0.5 to 50 wt%, preferably 1 to 30 wt%; and / or, The spray drying conditions in step (3) include: an inlet temperature of 90 to 240°C, preferably 110 to 200°C; and / or an outlet temperature of 70 to 130°C, preferably 95 to 110°C.

9. An olefin polymerization catalyst comprising: Component (A): an organoaluminum compound; Component (B): the metal composite containing silicon heterofluorene groups according to any one of claims 1 to 5 or the metal composite containing silicon heterofluorene groups obtained by the preparation method according to any one of claims 6 to 8.

10. The olefin polymerization catalyst according to claim 9, characterized in that The general formula of the organoaluminum compound of component (A) is AlR n X 3-n , wherein R is a C1-C18 hydrocarbon group, X is chlorine, bromine or iodine, and 0<n≤3; preferably, the organoaluminum compound is selected from at least one of triethylaluminum, triisobutylaluminum, tri-n-hexylaluminum, tri-n-octylaluminum, and diethylaluminum monochloride; and / or, The molar ratio of the component (A) to the component (B) is (5-450):1, preferably (15-250):1, wherein the component (A) is calculated based on the aluminum element contained therein, and the component (B) is calculated based on the titanium element contained therein.

11. A method for preparing the olefin polymerization catalyst according to claim 9 or 10, comprising: The olefin polymerization catalyst is obtained by mixing the components including the organic aluminum compound and the metal complex containing silicon heterofluorene groups.

12. An olefin polymerization catalyst according to claim 9 or 10 or an olefin polymerization catalyst obtained by the preparation method according to claim 11, used in olefin polymerization reactions.

Citation Information

Patent Citations

  • Catalyst used for ethylene polymerization or copolymerization, its preparation method and application

    CN100389134C

  • Catalyst component and catalyst for olefin polymerization, and preparation methods thereof

    CN106543303A

  • Catalyst for ethylene polymerization

    CN1493599A

  • Novel transition metal compound, catalyst for olefin polymerization containing the same, and method for producing propylene / ethylene-alpha-olefin block copolymer by using the catalyst

    CN101421286A

  • Preparation of polymerization catalyst activators utilizing indole-modified silica supports

    CN101511879A